Impacts of deforestation on the incidence of diseases in the Brazilian Amazon - Nilo Luiz Saccaro; Lucas Ferreira Mation; Patrícia Alessandra Morita Sakowski (Institute for Applied Economic Research (ipea), 2016)
The limited knowledge about the effect of deforestation on human health is an important gap for environmental and health management in Brazil and worldwide. In order to assess its occurrence and magnitude, we performed a panel analysis, linking data on deforestation and reportable diseases by municipality and year, covering 773 municipalities in the Amazon between 2004 and 2012. We conducted estimates separately for each disease, with the inclusion of controls for fixed effects of municipality, socioeconomic features and provision of public health services. Among the diseases that had sufficient data for analysis, we found that deforestation has a significant effect on leishmaniasis and malaria: on average, annual increases of 1% in the municipal deforested area lead to an increase between 14.5% and 23.2% in the incidence of malaria and between 5.12% and 9.26% in the incidence of leishmaniasis. On the other hand, statistically significant effects were not detected for diseases indicated as strong candidates by some authors. The results confirm the existence of health-related deforestation costs, although these do not apply to a wide range of diseases. We highlight the existence of deforestation costs related to health in the Amazon, which must be taken into account both in the management of public health and in decision making regarding natural capital.
Keywords: Q51; 330; environmental degradation; infectious diseases; public health